Daya Saing Ekspor Ikan Tuna Indonesia di Pasar Global - Baihaqi Yahya Nursya’ban; Fajar Adhany; Hafizd Razaan Zaidan; Renny Kurniawati (Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
Revealed Comparative Advantage (RCA) analysis is a key tool in assessing a country's competitiveness compared to others. This study uses RCA to measure Indonesia's comparative advantage in the global tuna market. The calculated RCA values show Indonesia's superiority in tuna production and exports, especially with a focus on fresh or chilled yellowfin tuna (Thunnus albacares) with HS Code 030232. The RCA values for Indonesia, Panama, the Philippines and the Netherlands are 200, 150, 50, 350, and 400, respectively. These results confirm that Indonesia has a comparative advantage in the international tuna market, which is supported by abundant natural resources, a large fishing workforce, and a history of successful tuna exports. Despite this, challenges remain, including overfishing, the impacts of climate change, and illegal, unreported, and unregulated (IUU) fishing. The decline in tuna production in Indonesia demands better fisheries management and international cooperation to address unsustainable practices. The Indonesian government's commitment to conservation is visible in the Tuna, Skipjack and Tuna Fisheries Management Plan. Overall, Indonesia's vibrant tuna export industry, supported by extensive marine resources, a large international market and robust infrastructure, shows significant potential. The government's commitment, combined with ongoing efforts to increase competitiveness through increased productivity, product quality, diversification and global promotion, positions Indonesia to strengthen its role as a major player in the global tuna export market.